The Effect Of 0.01% Atropine On Myopia Progression - Khalid, Amber (Journal of Rawalpindi Medical College, 2024)
Abstract Objective: Our study aims to assess the efficacy of a low dose of atropine (0.01%) in slowing the progression of myopia. Method: This prospective randomized controlled trial was conducted in the Ophthalmology department of Ziauddin University Hospital, Karachi. The study spanned a duration of four years, from July 1 2019 to June 30, 2023. A group of individuals presented at the eye outpatient department (OPD) with complaints of blurred vision underwent clinical examination and were diagnosed with myopia based on inclusion criteria. Data was collected and analyzed using SPSS 23, with the paired t-test employed for variable comparisons. Results: Our study analyzed and compared the results of the interventional group, where atropine eye drops (0.01%) were administered daily at bedtime, with the control group, which received Tear Natural II eye drops as a placebo. Patients were followed for three years, with two years dedicated to observing treatment responses and a one-year washout period for the drug. A comparison of baseline and 24-month means revealed an increase in myopia of 0.84 in the interventional group and 1.55 in the control group. Conclusion: Myopia is one of the leading causes of the development of sight-threatening conditions. Its progression can be slowed down by proper treatment with Atropine. The 0.01% dosage of atropine exhibited a favourable risk-benefit profile with minimal impact on visual function.